The Role of Imaging in Diagnosing Axial Spondyloarthritis - Khmelinskii, Nikita; Regel, Andrea; Baraliakos, Xenofon (Frontiers in Medicine, 2018)
Imaging has a central role in the diagnosis, management and follow-up of patients with axial spondyloarthritis (axSpA). For the early diagnosis of axSpA magnetic resonance imaging is of upmost relevance. While no novel imaging techniques were developed during the past decade, improvements to the existing modalities have introduced. This report provides an overview of the applications and limitations of the existing imaging modalities.